Impact of Human Resource Development on Public Service Through Employee Performance Of Center Mamuju - Nimrah Rahmayanti Yusuf; Widyawati Widyawati; Nurlaela Nurlaela (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Public organizations as a place for providing services to the community must be supported by quality human resources. This is inseparable from the human resource development system, in creating superior human resources and having good performance so that the services provided can increase public satisfaction. This research is a quantitative type of research, which is conducted at the Civil Service and Civil Service Agency, Population and Civil Registry Office and five District Offices in Central Mamuju Regency. The sample in this study amounted to 102 people. Data collection was carried out through distributing questionnaires, observations, interviews and supporting documents related to the research topic. The results showed that the development of human resources through employee performance had an influence on the quality of public services in Central Mamuju Regency with an F calculated value of 15.668. greater than the F table, which is 3.09. For the probability value, the value is 0,000, smaller than 0.05.